2021
DOI: 10.1272/jnms.jnms.2021_88-413
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Hypoganglionosis of the Colon: A Case Report

Abstract: A 64-year-old female was admitted to the hospital with constant abdominal pain. She had been previously hospitalized five times in 2 years with similar symptoms. Computed tomography revealed dilatation and fecal impaction from the ileum to the transverse colon. A barium enema and simultaneous ileus tube radiography demonstrated a segment of narrow descending-sigmoid colon. Colonoscopy did not show any mucosal change. These symptoms did not improve with conservative therapy when a descending and sigmoid colecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Changes in Cajal interstitial cell numbers are described in patients with idiopathic megacolon or chronic constipation by numerous studies and suggested as an etiopathogenic basis [18][19][20][21][22][23][24]. They are considered a true intestinal pacemaker ("little brain" at the enteral level); however, starting from the premise that their number decreases physiologically with age anyway and by the fact that a number of other communications do not confirm their involvement in the etiopathogenesis of idiopathic megacolon, this theory remains for the moment only a new subject of controversy [8].…”
Section: Cajal Cellsmentioning
confidence: 99%
“…Changes in Cajal interstitial cell numbers are described in patients with idiopathic megacolon or chronic constipation by numerous studies and suggested as an etiopathogenic basis [18][19][20][21][22][23][24]. They are considered a true intestinal pacemaker ("little brain" at the enteral level); however, starting from the premise that their number decreases physiologically with age anyway and by the fact that a number of other communications do not confirm their involvement in the etiopathogenesis of idiopathic megacolon, this theory remains for the moment only a new subject of controversy [8].…”
Section: Cajal Cellsmentioning
confidence: 99%